ERADICATION EFFORTS BY POLICE ON CRIMINAL ACT OF ABORTION COMMITTED BY CHILDREN AT REGIONAL AREA OF NORTH SUMATERA POLICE STATION - Rahardian Ayu Saputri (Ilmu Hukum Prima (IHP), 2018)
Abortion is a serious problem as viewed from the high number of abortions from year to year in Indonesia. The annual number of fetal killings has reached 3 million, a number that is not small considering the magnitude of the pregnancy rate in Indonesia. Many believe that the unplanned factors driving abortion are pregnancy from premarital sex, rape, and failed contraception. The term abortion or abortion provocatus comes from Latin, which means abortion because of intent. In the Criminal Code and Law No. 36 of 2009 concerning Health, criminal sanctions for abortion perpetrators have been, but in the health law, women are given exemptions for abortions as stated in article 75 paragraph 2. In addition, police countermeasures against criminal acts of abortion carried out by children, is very important role of law enforcement, family, community in providing guidance to minors, because abortion is clearly contrary to norms, religion is the biggest problem which until now still complicates agreement on problem management policies abortion, because of that, illegal abortion that is not in accordance with medical methods still goes on and remains a big problem that still threatens women in their reproductive period, but it is very important the role of the family and the environment in the effort to overcome abortion committed by child.